The narrative of nursing students in their Supervised Curricular Internship portfolios - Nádia Frazão Rossi; Cinira Magali Fortuna; Silvia Matumoto; Franciele Maia Marciano; Jael Bernardes da Silva; Juliana Sterci da Silva (Universidade Federal de Goias, 2014)
The critical-reflective training of nurses is a challenge. The reflective portfolio is an instrument used for developing this capacity. The aim of this qualitative study was to identify the types of narratives present in such portfolios and analyze the reflections of students enrolled in the Supervised Curricular Internship. Eleven portfolios were analyzed, and the narratives found were descriptive, reflective and descriptive, reflective and dialogic, and critical with subsequent thematic analysis. We identified four types of narratives. Reflections were focused around three thematic categories: an analysis of the internship's field of work; assimilation and analysis of the nursing professional's work; and what was learned throughout the Supervised Curricular Internship. The relevant aspects of the internship experience were apprehended and systematized through the portfolios, although more in-depth critical reflection is needed. The analysis of narrative types presented by students can contribute to guiding the process of nursing training evaluation towards critical reflection. doi: 10.5216/ree.v16i3.25691.